Composite organic electrode material, preparation method and application
By combining the conjugated carbon framework with a high crystallinity conductive polymer layer, the solubility, conductivity and winding problems of organic electrode materials are solved, and a high-performance composite organic electrode material is achieved.
Patent Information
- Application Number
- CN202411974632.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-02-07
AI Technical Summary
Existing organic electrode materials have problems in solubility, conductivity and spatial winding, resulting in insufficient performance.
A composite organic electrode material that combines a conjugated carbon framework with a high crystallinity conductive polymer layer is used to improve the mechanical strength and electrical conductivity of the material through conjugation and reduce spatial wrapping.
The electrochemical properties of composite organic electrode materials are significantly improved, including capacity, magnification and cyclic stability, while improving mechanical strength and conductivity.
Smart Images

Figure CN119400861A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy technology, and in particular to a composite organic electrode material, a preparation method and an application thereof. Background Art
[0002] Compared with traditional inorganic electrode materials, organic electrode materials have significant advantages such as lightweight, adjustability and environmental friendliness. Their molecular structure can be optimized according to demand, the production cost is relatively low, and the synthesis process has little impact on the environment. Existing research has shown that organic electrode materials show great potential in theoretical capacity, cycle stability and rate. However, small molecule organic materials face serious solubility problems, and long-chain organic polymers have problems such as poor conductivity and easy entanglement and agglomeration. Summary of the invention
[0003] The present invention aims to solve the technical problems existing in the prior art. To this end, the present invention proposes a composite organic electrode material, which includes a conjugated carbon skeleton, and a conductive polymer layer coated on the outer layer of the conjugated carbon skeleton and containing at least two copolymer blocks; the conjugated carbon skeleton has a long chain or ring structure with single bonds and double bonds arranged alternately, and the conductive polymer layer contains at least one unsaturated ring and has a crystallinity of ≥30%, and can have a strong conjugation effect with the conjugated carbon skeleton. The conjugated carbon skeleton provides support for the polymer and reduces spatial entanglement to obtain high mechanical strength and high electrical conductivity; the conductive polymer of the copolymer block can grow to a certain crystalline thickness on the conjugated carbon skeleton material, thereby having a strong conjugation effect with the carbon skeleton material, improving the reaction kinetics and increasing the electrochemical active area, thereby improving the performance of the composite organic electrode material as a whole.
[0004] The invention also provides a method for preparing the composite organic electrode material.
[0005] The present invention also provides a secondary battery comprising the composite organic electrode material.
[0006] According to an embodiment of the first aspect of the present invention, a composite organic electrode material is provided, which comprises a conjugated carbon skeleton and a conductive polymer layer coated on the outer layer of the conjugated carbon skeleton and containing at least two copolymer blocks; the conjugated carbon skeleton has a long chain or ring structure in which single bonds and double bonds are alternately arranged, and the conductive polymer layer contains at least one unsaturated ring and has a crystallinity of ≥30%, and can undergo strong conjugation with the conjugated carbon skeleton.
[0007] According to some embodiments of the present invention, the conjugated carbon skeleton is one of carbon nanotubes, graphite, and graphene.
[0008] The conjugated carbon skeleton has a long chain or ring structure with alternating single bonds and double bonds, allowing π electrons to move freely throughout the skeleton; the conductive polymer layer has at least one unsaturated ring, and can have a strong conjugation effect with the above-mentioned conjugated carbon skeleton, which improves the reaction kinetics and increases the electrochemical active area, thereby improving the performance of the composite organic electrode material as a whole. The conjugated carbon skeleton material is a rigid material, which supports the growth of copolymer conductive polymers with crystalline properties through non-bonding effects, and can guide the self-assembly process of the polymer itself to form a higher degree of crystallinity, reducing the random winding probability of the organic long chain in space. On the other hand, the conjugated carbon skeleton material can adjust the electron cloud of the conductive polymer that also has conjugation ability through its own conjugated π electrons, improve its conductive properties, and thus further obtain a composite organic electrode material with high conductive properties. The self-assembled conductive polymer layer is wrapped in the outer layer of the carbon skeleton, exposing the electrochemically active thiophene ring group. This coated non-bonded connection structure can ensure effective support while not consuming the unsaturated bonding ability of the active group thiophene ring, so it does not consume the potential as an electrode material. At the same time, many studies have shown that there is further synergy between carbon materials containing conjugated structures and organic conjugated conductive polymers, which can further improve the key properties of electrode materials including capacity, rate and cycle.
[0009] According to an embodiment of the second aspect of the present invention, there is provided a method for preparing a composite organic electrode material, comprising the following steps: S1: dispersing the conjugated carbon skeleton material in tetrahydrofuran and / or chloroform to obtain a dispersion A; S2: Add 2,5-dihalo-(3-alkyl)thiophene and alkyl magnesium halide of equal molar mass to dispersion A, mix and react for 0.1-5h to obtain solution B; S3: adding a polymerization catalyst to the solution B and reacting for 0.5 to 24 hours to obtain a solution C; S4: mixing 2,5-dihalo-(3-alkyl)thiophene different from S2 and alkyl magnesium halide of equal molar mass in the dispersion A for reaction for 0.1 to 5 hours to obtain solution D; S5: mixing the solution C and the solution D, reacting at 5-80° C. for 1-24 h, to obtain a polymer-containing solution E; S6: adding the obtained solution E dropwise into methanol and / or ethanol to precipitate the product, and purifying it with methanol and / or n-hexane, and then drying it to obtain the composite organic electrode material.
[0010] In the design of the entire preparation method, the organic layer was first grown in situ on the conjugated carbon skeleton so that they could better play a synergistic role. At the same time, in the construction of the conductive polymer structure, a thiophene-based polymer with a high crystallization tendency was designed, and other conductive polymers with at least one unsaturated ring and with crystallinity can also be selected. Because this polymer can self-assemble to form a certain crystal plane structure. This structure is more likely to interact with the pre-dispersed conjugated skeleton with a consistent effect, which is manifested as an improvement in the overall performance of the material. At the same time, the block conductive polymer can easily regulate the physicochemical properties of the organic layer by adjusting the feed ratio and catalyst dosage when constructing different blocks, providing convenience for subsequent process adjustments. The pre-dispersed carbon skeleton material will serve as a heterogeneous nucleation site when the long-chain polymer nucleates, grows and precipitates, because this method requires the least energy. This greatly alleviates the disadvantages of the traditional unsupported block material preparation method, because in the traditional method, this polymer will precipitate successively and serve as a new nucleation site, thereby increasing the probability of entanglement and agglomeration, thereby limiting the exposure of the crystal surface and cannot be used as a high-performance electrode material. At the same time, the conjugation between the copolymer and the skeleton regulates the precipitation orientation of organic matter to a certain extent, and will preferentially make the conjugated planes with strong interaction forces arranged in parallel. This process can also be regarded as actively regulating the molecular self-assembly process of the organic chain. In this way, the target composite organic electrode material with strong conjugation can be obtained.
[0011] According to some embodiments of the present invention, the content of the conjugated carbon skeleton material in the dispersion A in step S1 is 0.1-100 mg / ml.
[0012] According to some embodiments of the present invention, the conjugated carbon skeleton material in the dispersion A in step S1 is one of carbon nanotubes, graphite and graphene.
[0013] According to some embodiments of the present invention, the alkyl group of the 2,5-dihalo-(3-alkyl)thiophene and alkylmagnesium halide described in steps S2 and S4 may be, for example, a straight chain or branched chain having 1 to 24 carbon atoms, and may be, for example, methyl, ethyl, n-propyl, n-butyl, sec-butyl, tert-butyl, n-hexyl, 2-ethylhexyl, cyclohexyl, n-decyl, n-undecyl, n-dodecyl, n-tridecyl, n-tetradecyl, n-hexadecyl, n-octadecyl or dodecyl alkyl. Halogen may be fluorine, chlorine, bromine, and iodine.
[0014] According to some embodiments of the present invention, the molar ratio of the two different 2,5-dihalo-(3-alkyl)thiophenes in step S2:S4 is 1:0.1-10.
[0015] According to some embodiments of the present invention, it is characterized in that: the polymerization reaction catalyst in step S3 is one of Pd(PPh3)2Cl2, Pd(OAc)2, Ni(dppp)Cl2, Ni(PPh3)3Cl2, or a mixture of more than one of them.
[0016] According to an embodiment of the third aspect of the present invention, a secondary battery is provided, wherein the raw materials for preparing the secondary battery include the composite organic electrode material provided by the first aspect of the present invention, and the material is prepared according to the method provided by the second aspect of the present invention.
[0017] The secondary battery comprising the composite organic electrode material according to the embodiment of the present invention has at least the following beneficial effects: (1) Excellent electrochemical properties including high capacity, rate, stable cycle, etc.: In the composite organic electrode material provided by the present invention, a copolymer block structure with crystalline properties is selected when designing the conductive polymer layer, which improves the orderliness and electrochemical performance of the organic layer. This is because such conductive polymers tend to be regularly arranged in space to form crystal planes, which directly reduces the entanglement between long-chain polymers and improves the number of ion migration and conductivity. At the same time, when the polymer is used as an electrode active material, p-type or n-type conversion will occur. This process does not involve bond rearrangement and has excellent kinetic rate, making it suitable for high-performance secondary batteries.
[0018] (2) Increased mechanical strength and conductivity of composite organic electrode materials: The introduction of conjugated carbon skeleton materials as polymer growth skeletons enhances the mechanical strength of composite organic electrode materials. On the one hand, it reduces the probability of disordered entanglement in space, which is beneficial to solving the problem of long chain agglomeration. At the same time, the conjugated structure of the carbon skeleton can interact with the highly crystalline conductive polymer layer, thereby improving the stability of the composite organic electrode material in practical applications.
[0019] (3) Adaptable to multiple application scenarios and adjustable: According to the synthesis conditions of the conductive polymer, different synthetic monomers, and different feed ratios, the interplanar spacing and crystallinity of the organic material can be flexibly adjusted, thereby increasing or reducing the stable storage space for ions to adapt to different ions, so as to meet the application requirements of different ion batteries or positive and negative electrodes. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solution of the present invention, the drawings required for use in the implementation mode will be briefly introduced below. Obviously, the drawings described below are only some implementation modes of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1It is the infrared spectrum of the composite organic electrode material prepared in Example 1.
[0022] Figure 2 This is a TEM image of the organic composite electrode material prepared in Example 1 of the present invention.
[0023] Figure 3 This is a specific capacity-voltage diagram of the organic composite electrode material prepared in Example 2 of the present invention applied to a lithium battery negative electrode.
[0024] Figure 4 This is a specific capacity-voltage diagram of the organic composite electrode material prepared in Example 5 of the present invention when applied to a sodium battery negative electrode.
[0025] Figure 5 This is a specific capacity-voltage diagram of the organic composite electrode material prepared in Example 5 of the present invention when applied to a lithium battery positive electrode.
[0026] Figure 6 It is the XRD spectrum of the organic composite electrode material prepared in Example 2 and Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0027] The following are preferred embodiments of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications may be made without departing from the principles of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.
[0028] Example 1 In this example, an organic composite electrode material was prepared. The specific steps are as follows: S1. Disperse 100 mg of carbon nanotubes in 100 ml of tetrahydrofuran to obtain dispersion A.
[0029] S2. Under N2 atmosphere, add 2,5-dibromothiophene (5 mmol) and 2.5 ml isopropylmagnesium chloride (5 mmol) to 20 ml solvent A. The reaction time is 1 hour at room temperature. S3. Heat the system to 50°C, then add the catalyst 1,3-bis(diphenylphosphinomethane)nickel dichloride (0.05 mmol), and react at this temperature for 2 h to obtain solution B; S4. Add 2,5-dibromo-3-butylthiophene (5 mmol) and 2.5 ml of isopropylmagnesium chloride (2 mol / l) to dispersion A and react at 0°C for 1 h. S5. The solution obtained in S4 was mixed with solution B and reacted at 40°C for 6 h; S6. Add excess methanol to precipitate. The precipitated product is purified by Soxhlet extraction in methanol and n-hexane for 24 hours, respectively, and then dried to obtain the target composite organic electrode material.
[0030] Example 2 This example prepares an organic composite electrode material, and the specific steps are different from those in Example 1 in that: (1) Step S1 is replaced by: dispersing 10 mg of carbon nanotubes in 100 ml of tetrahydrofuran to obtain dispersion A; (2) The amount of 2,5-dibromothiophene in step S2 is adjusted to 15 mmol, and the molar ratio of the amount of 2,5-dibromo-3-butylthiophene in step S4 is 3:1; (3) The reaction temperature in step S3 is adjusted to 25°C; (4) The reaction time in step S5 is adjusted to 10 h; (5) The isopropylmagnesium chloride in steps S2 and S5 was replaced with methylmagnesium bromide of equal molar mass, and the reaction time at room temperature was extended to 2 hours.
[0031] Example 3 This example prepares an organic composite electrode material, and the specific steps are different from those in Example 1 in that: (1) Step S1 is replaced by: dispersing 100 mg of graphene in 100 ml of chloroform to obtain dispersion A; (2) 5 mmol of 2,5-dibromothiophene in step S2 was replaced with 5 mmol of 2,5-diiodo-3-hexylthiophene, and the molar ratio with 2,5-dibromo-3-butylthiophene in step S4 was kept at 1:1; (3) The reaction time in step S3 is adjusted to 4 h; (4) The reaction time in step S5 is adjusted to 10 h; (5) The isopropylmagnesium chloride in steps S2 and S5 is replaced by cyclohexylmagnesium iodide of equal molar mass.
[0032] Example 4 This example prepares an organic composite electrode material, and the specific steps are different from those in Example 1 in that: (1) Step S1 is replaced by: dispersing 100 mg of graphite in 100 ml of tetrahydrofuran to obtain dispersion A; (2) In step S4, 5 mmol of 2,5-dibromo-3-butyldibromothiophene was replaced with 5 mmol of 2,5-dichloro-3-decylthiophene, and the molar ratio with 2-bromo-5-iodo-butylthiophene in S2 was kept at 1:1; (3) The reaction time in step S5 is adjusted to 10 h; (4) Step S6 is replaced by using ethanol to precipitate; (5) The isopropylmagnesium chloride in steps S2 and S5 is replaced by n-butylmagnesium bromide of equal molar mass.
[0033] Example 5 This example prepares an organic composite electrode material, and the specific steps are different from those in Example 1 in that: (1) Step S1 is replaced by: dispersing 50 mg of carbon nanotubes in 100 ml of tetrahydrofuran to obtain dispersion A; (2) In step S4, 5 mmol of 2,5-dibromo-3-butyldibromothiophene was replaced with 20 mmol of 2,5-dibromo-3-dodecylthiophene, and the molar ratio of 2,5-dibromothiophene to 2,5-dibromothiophene in step S2 was maintained at 4:1; (3) The reaction time in step S5 is adjusted to 10 h.
[0034] Example 6 This example prepares an organic composite electrode material, and the specific steps are different from those in Example 1 in that: In step S3, the catalyst 1,3-bis(diphenylphosphine) nickel dichloride (Ni(dppp)Cl 2, 0.05 mmol) was replaced by bistriphenylphosphine palladium dichloride (Pd(PPh3)2Cl2, 0.05 mmol).
[0035] Comparative Example 1 In this example, an organic composite electrode material is prepared. The specific steps are different from those in Example 1 in that a dispersion containing a carbon skeleton material is not used as a synthetic solvent, but is replaced by a pure tetrahydrofuran solvent. The comparison sample thus obtained does not contain a carbon skeleton material and is a common block organic comparison sample.
[0036] Comparative Example 2 In this example, an organic composite electrode material was prepared. The specific steps were different from those in Example 1 in that steps S4 and S5 were not performed, the monomer in S2 was changed to 5 mmol of 2,5-dibromo-3-butyldibromothiophene, and the reaction time of S3 was extended to 8 h to prepare a composite electrode material comparison sample without a block.
[0037] Electrode performance test: In the electrode performance test comparison, the composite organic electrode materials in Examples 1 to 6 and Comparative Examples 1 to 2 were mixed with PVDF and carbon black in the same mass ratio of 6:3:1 to form a uniform slurry, and copper foil was used as the current collector to obtain the negative electrode sheet, which was then prepared into a button half-cell with a lithium sheet and an electrolyte LiPF6 (1.0 M LiPF6 in EC:DMC:EMC=1:1:1) in a glove box under an argon atmosphere.
[0038] At 25°C, the charge and discharge cycle characteristics of button batteries were tested using a blue power test cabinet. The current density was set to 50mA / g, and lithium button half-cells were used as an example to test and compare the gram-specific capacity and coulomb efficiency of the first charge and first discharge of each battery cycled at 0.01-3V. The current density was set to 100mA / g, and the stable capacity during the cycle and the capacity retention rate after 200 charge and discharge cycles were tested.
[0039] The above test results are shown in Table 1.
[0040] Table 1 Performance of lithium battery negative electrode materials obtained in Examples 1 to 6 and Comparative Examples 1 to 2
[0041] According to the above results, the organic composite electrode material prepared by the preparation method provided by the present invention has a greatly improved charge and discharge capacity, which is attributed to the conjugated synergy between the excellent conjugated carbon skeleton and the highly crystalline conductive polymer, which can effectively expose the active sites and increase the reaction rate. It can be expected that the above composite organic electrode material can be used as an excellent negative electrode material for lithium-ion batteries. The above prepared lithium button battery is charged and discharged at 2.2V~3.8V, as shown in FIG. Figure 5 As shown, it is explained that the above composite organic electrode material can also be used in the positive electrode.
[0042] At the same time, the organic electrode plate was paired with the sodium plate and the electrolyte NaPF6 (1.0 M NaPF6in EC:DMC:EMC=1:1:1) to prepare a sodium button half-cell in a glove box under an argon atmosphere. The charge and discharge cycle was completed at a voltage of 0.01-3V. Figure 4 As shown, the battery exhibits an initial discharge capacity of 230 mAh / g, indicating that the above organic composite can be used as an active electrode material for sodium ion batteries or other ion batteries.
[0043] Figure 1 is the infrared spectrum of the composite organic electrode material prepared in Example 1. At 750 cm -1 The absorption peak of the CS bond of the thiophene ring can be observed at 2915 cm -1 The nearby peaks come from the stretching vibration absorption of the CH bond of the side chain at position 3 of the thiophene ring. -1 OH absorption from the hydroxylated wall of carbon nanotubes was observed, which indicates that the composite organic electrode material of thiophene-butylthiophene copolymer block organic matter and multi-walled carbon nanotubes was successfully obtained.
[0044] Figure 2This is a TEM image of the organic composite electrode material prepared in Example 1 of the present invention. It can be observed that the polymer is based on the carbon nanotubes as the skeleton and grows around the tubular structure, which illustrates the supporting role of the carbon nanotubes.
[0045] Figure 3 This is a specific capacity-voltage diagram of the organic composite electrode material prepared in Example 2 of the present invention applied to a negative electrode of a lithium battery. The specific capacity of the material is as high as ~680 mAh / g, which illustrates the application of the material in a negative electrode of a lithium battery.
[0046] Figure 4 The specific capacity-voltage diagram of the organic composite electrode material prepared in Example 5 of the present invention applied to the negative electrode of sodium battery is shown, which illustrates that the application of such materials can be expanded to other secondary batteries besides lithium battery by adjusting the organic components and proportions.
[0047] Figure 5 The graph is a specific capacity-voltage diagram of the organic composite electrode material prepared in Example 5 of the present invention and applied to the positive electrode of lithium battery, which shows that such material can be applied in the positive electrode of secondary battery.
[0048] Figure 6 It is the XRD spectrum of the organic composite electrode material prepared in Example 2 of the present invention and Comparative Example 1. This figure illustrates that the conductive polymer can be in-situ constructed on the carbon skeleton material using the preparation method to form a high crystallinity.
Claims
1. A composite organic electrode material, characterized in that: The composite organic electrode material includes a conjugated carbon skeleton and a conductive polymer layer coated on the outer layer of the conjugated carbon skeleton and containing at least two copolymer blocks; the conjugated carbon skeleton has a long chain or ring structure with single bonds and double bonds arranged alternately, and the conductive polymer layer contains at least one unsaturated ring and has a crystallinity of ≥30%, and can have a strong conjugation effect with the conjugated carbon skeleton.
2. The composite organic electrode material according to claim 1, characterized in that: The conjugated carbon skeleton is one of carbon nanotubes, graphite and graphene.
3. A method for preparing a composite organic electrode material as claimed in claim 1-2, characterized in that: The preparation method comprises the following steps: S1: dispersing the conjugated carbon skeleton material in tetrahydrofuran and / or chloroform to obtain a dispersion A; S2: Add 2,5-dihalo-(3-alkyl)thiophene and alkyl magnesium halide of equal molar mass to dispersion A, mix and react for 0.1-5h to obtain solution B; S3: adding a polymerization catalyst to the solution B and reacting for 0.5 to 24 hours to obtain a solution C; S4: mixing 2,5-dihalo-(3-alkyl)thiophene different from S2 and alkyl magnesium halide of equal molar mass in the dispersion A for reaction for 0.1 to 5 hours to obtain solution D; S5: mixing the solution C and the solution D, reacting at 5-80° C. for 1-24 h, to obtain a polymer-containing solution E; S6: adding the obtained solution E dropwise into methanol and / or ethanol to precipitate the product, and purifying it with methanol and / or n-hexane, and then drying it to obtain the composite organic electrode material.
4. The method for preparing a composite organic electrode material according to claim 3, characterized in that: The content of the conjugated carbon skeleton material in the dispersion A in step S1 is 0.1-100 mg / ml.
5. The method for preparing a composite organic electrode material according to claim 3, characterized in that: The alkyl group of the 2,5-dihalo-(3-alkyl)thiophene and the alkyl magnesium halide described in steps S2 and S4 is one of methyl, ethyl, n-propyl, n-butyl, sec-butyl, tert-butyl, n-hexyl, 2-ethylhexyl, cyclohexyl, n-decyl, n-undecyl, n-dodecyl, n-tridecyl, n-tetradecyl, n-hexadecyl, n-octadecyl, and dodecyl alkyl, and the halogen is one of fluorine, chlorine, bromine, and iodine.
6. The method for preparing a composite organic electrode material according to claim 3, characterized in that: The molar ratio of the two different 2,5-dihalo-(3-alkyl)thiophenes in step S2:S4 is 1:0.1-10.
7. The method for preparing a composite organic electrode material according to claim 3, characterized in that: The polymerization reaction catalyst in step S3 is one or more of Pd(PPh3)2Cl2, Pd(OAc)2, Ni(dppp)Cl2, and Ni(PPh3)3Cl2.
8. A secondary battery, characterized in that: The secondary battery comprises the composite organic electrode material as described in any one of claims 1 to 2.